2016
DOI: 10.1002/cncr.29779
|View full text |Cite
|
Sign up to set email alerts
|

Ototoxicity and cancer therapy

Abstract: Ototoxicity is a well-established toxicity associated with a subgroup of antineoplastic therapies that includes platinum chemotherapy, radiation or surgery involving the ear and auditory nerve, and supportive care agents such as aminoglycoside antibiotics and loop diuretics. The reported prevalence of ototoxicity in patients who have received potentially ototoxic therapy ranges from 4% to 90% depending on factors such as age of the patient population, agent(s) used, cumulative dose, and administration techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
129
1
11

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(159 citation statements)
references
References 71 publications
7
129
1
11
Order By: Relevance
“…Tinnitus is a common condition, especially in cancer treatment, caused by chemotherapy drugs and radiotherapy [17,[20][21][22]. The present study did not reveal relation between tinnitus and hearing loss, in contrast investigators have reported this relation [20].…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Tinnitus is a common condition, especially in cancer treatment, caused by chemotherapy drugs and radiotherapy [17,[20][21][22]. The present study did not reveal relation between tinnitus and hearing loss, in contrast investigators have reported this relation [20].…”
Section: Discussioncontrasting
confidence: 94%
“…Indeed, investigators reported that most of hearing loss in oncology survivors is sensorineural [5,[16][17][18], which affects inner ear, particularly outer hair cells [3,17]. Inner ear is the most susceptible organ in a durable long-term radiotherapy and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Para simplificar la interpretación de las pruebas audiométricas se han propuesto diferentes clasificaciones, que por buscar precisión han multiplicado la diversidad, provocando confusión a la hora de comparar los resultados. Nosotros hemos escogido la escala de Brock et al (1991) [3] y en ocasiones la de Chang y Chinosornvatana (2010) [4], porque resultan sencillas de aplicar y de entender, siendo ampliamente utilizadas, aunque sería preferible poder definir y utilizar un único sistema de aná-lisis [25][26]. Durante los últimos años se viene investigando sobre la posibilidad de adaptar las otoemisiones acústicas transitorias (OEAT) y los productos de distorsión (PD), como técnicas de cribado del daño auditivo [27].…”
Section: Discussionunclassified
“…It is also possible that the exact incidence is under-reported based on comorbid conditions of the patient or gradual use in previous studies might have only captured Grade III and IV. Because mutations in c-Kit constitute the intended molecular target for imatinib in the treatment of GIST, it is possible that the pharmacologic inhibition of c-Kit might negatively affect hearing, probably a neurotoxic effect on the auditory nerve [7-10]. Future studies of the effect of imatinib and/or TK inhibition on the inner ear as a possible cause of imatinib-related ototoxicity are indicated.…”
Section: Discussionmentioning
confidence: 99%